2020
DOI: 10.1007/s00127-020-01842-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of refugee status and mental disorders regarding subsequent labour market marginalisation: a register study from Sweden

Abstract: Purpose This study aimed to assess the role of refugee status and specific mental disorders regarding subsequent labour market marginalisation. Methods Prospective cohort study of all refugees (n = 216,930) and Swedish-borns (n = 3,841,788), aged 19-60 years, and resident in Sweden in 2009. Hazard ratios (HRs) with 95% Confidence Intervals (CIs) for long-term unemployment (> 180 days) and disability pension (DP) were calculated with Cox regression analyses. Results Mental disorders were more prevalent in refug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 12 publications
4
21
0
Order By: Relevance
“…Moreover, given the fit of the alternative model, it is more probable that the appearance of PTSD cases explains the unemployment condition. This finding is novel in the literature reviewed and supports ideas such as the lack of clarity when the stress-unemployment cycle could begin [7,31], and the relationship between stressors, unemployment and mental health tends to be interdependent once it starts [7,9,32], in refugees [33,34], immigrants [35], men [36] and women veterans [37], and social workers, to name a few cases. For example, studies conducted on Iraqi refugees show that exposure before and after the event predicts unemployment by 91% [7].…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, given the fit of the alternative model, it is more probable that the appearance of PTSD cases explains the unemployment condition. This finding is novel in the literature reviewed and supports ideas such as the lack of clarity when the stress-unemployment cycle could begin [7,31], and the relationship between stressors, unemployment and mental health tends to be interdependent once it starts [7,9,32], in refugees [33,34], immigrants [35], men [36] and women veterans [37], and social workers, to name a few cases. For example, studies conducted on Iraqi refugees show that exposure before and after the event predicts unemployment by 91% [7].…”
Section: Discussionsupporting
confidence: 56%
“…As they therefore often end up in jobs below their formal educational level, this might contribute to high levels of both long-term unemployment as well as general labour market marginalisation as over qualification has been reported as a strong risk factor for health deterioration [38]. Despite efforts with free language training to all migrants, language barriers may still be a reason for discrepancies in long-term unemployment between subgroups of migrants as the training is voluntary, and some groups of migrants are underrepresented in those classes [6,39] In a previous study from our research group, we found that the risk of long-term unemployment among refugees with a common mental disorder was around two times higher compared to Swedish-born individuals with no mental disorder [40]. The aim of this study was to go one step further and deepen the analyses about pathways to labour market marginalisation specifically among individuals with a common mental disorder.…”
Section: Long-term Unemploymentmentioning
confidence: 89%
“…In a previous study from our research group, we found that the risk of long-term unemployment among refugees with a common mental disorder was around two times higher compared to Swedish-born individuals with no mental disorder [ 40 ]. The aim of this study was to go one step further and deepen the analyses about pathways to labour market marginalisation specifically among individuals with a common mental disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The sub-group of refugees contains people who are defined by the UNCHR as “someone who is unable or unwilling to return to their country of origin owing to a well-founded fear of being persecuted for reasons of race, religion, nationality, membership of a particular social group, or political opinion” ([ 3 ], page 3). This group is at high risk of developing mental health problems [ 4 , 5 , 6 , 7 ]. To illustrate, the prevalence of common mental health disorders among refugees is about twice as high compared to migrant worker populations [ 8 ].…”
Section: Introductionmentioning
confidence: 99%